N-type SnO2 nanosheets standing on p-type carbon nanofibers: a novel hierarchical nanostructures based hydrogen sensor1. Issue 79 (28th August 2015) - Wang, Zhaojie; Liu, Siyuan; Jiang, Tingting; Xu, Xiuru; Zhang, Jun; An, Changhua; Wang, Ce
<x xml:space="preserve">Abstract</x> The synergistic relationship of n-type SnO2 nanosheets and p-type CNFs offers an exciting pathway to enhanced sensors.